Hydrophobically Modified Chitosan - Shedge, Aarti S.; Badiger, Manohar V. (Hydrophobically Modified Chitosan, 2014)
Hydrophobically modified chitosan was prepared using the hydrophobic compound derived from natural resource material such as cashew nut shell liquid. Chitosan was modified using 3-pentadecyl cyclohexane carbaldehyde to different extents (2, 3, and 5 mol%). Solution properties of hydrophobically modified chitosan were studied by rheology and light scattering. These indicated the aggregation behavior above the critical association concentration. Further, it was concluded that above the critical association concentration, the dynamics of the network formed due to the associations slowed down significantly.